Meaningful use of imaging resources to rule out cerebral venous sinus thrombosis after ChAdOx1 COVID-19 vaccination: Evaluation of the AHA diagnostic algorithm with a clinical cohort and a systematic data review. (August 2022) - Fervers, Philipp; Kottlors, Jonathan; Persigehl, Thorsten; Lennartz, Simon; Maus, Volker; Fischer, Sebastian; Styczen, Hanna; Deuschl, Cornelius; Schlamann, Marc; Mpotsaris, Anastasios; Zubel, Seraphine; Schroeter, Michael; et al.
Highlights: Evaluation for post-vaccination cerebral thrombosis depletes radiological resources. The AHA algorithm yielded 100% sensitivity to diagnose this severe complication. The number of neuroradiological exams needed to diagnose one case was 1:113 (NND). Thrombocytopenia or d-dimer as a gatekeeper for imaging lowered the NND to 1:68. Abstract: Vaccine-induced immune thrombotic thrombocytopenia (VITT) with cerebral venous thrombosis (CVST) is an improbable (0.0005%), however potentially lethal complication after ChAdOx1 vaccination. On the other hand, headache is among the most frequent side effects of ChAdOx1 (29.3%). In September 2021, the American Heart Association (AHA) suggested a diagnostic workflow to facilitate risk-adapted use of imaging resources for patients with neurological symptoms after ChAdOx1. We aimed to evaluate the AHA workflow in a retrospective patient cohort presenting at four primary care hospitals in Germany for neurological complaints after ChAdOx1. Scientific literature was screened for case reports of VITT with CVST after ChAdOx1, published until September 1st, 2021. One-hundred-thirteen consecutive patients (77 female, mean age 38.7 +/− 11.9 years) were evaluated at our institutes, including one case of VITT with CVST. Further 228 case reports of VITT with CVST are published in recent literature, which share thrombocytopenia (225/227 reported) and elevated d-dimer levels (100/101 reported). The AHA workflow would have recognized all VITT cases with CVST (100% sensitivity), the number needed to diagnose (NND) was 1:113. Initial evaluation of thrombocytopenia or elevated d-dimer levels would have lowered the NND to 1:68, without cost of sensitivity. Hence, we suggest that in case of normal thrombocyte and d-dimer levels, the access to further diagnostics should be limited by the established clinical considerations regardless of vaccination history.